Rethinking capital regulation: The case for a dividend prudential target - Manuel Mu\~noz (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
The paper investigates the effectiveness of dividend-based macroprudential rules in complementing capital requirements to promote bank soundness and sustained lending over the cycle. First, some evidence on bank dividends and earnings in the euro area is presented. When shocks hit their profits, banks adjust retained earnings to smooth dividends. This generates bank equity and credit supply volatility. Then, a DSGE model with key financial frictions and a banking sector is developed to assess the virtues of what shall be called dividend prudential targets. Welfare-maximizing dividend-based macroprudential rules are shown to have important properties: (i) they are effective in smoothing the financial and the business cycle by means of less volatile bank retained earnings, (ii) they induce welfare gains associated to a Basel III-type of capital regulation, (iii) they mainly operate through their cyclical component, ensuring that long-run dividend payouts remain unaffected, (iv) they are flexible enough so as to allow bank managers to optimally deviate from the target (conditional on the payment of a sanction), and (v) they are associated to a sanctions regime that acts as an insurance scheme for the real economy.
Keywords: E44; E61; G21; G28; G35; 330; macroprudential regulation; capital requirements; dividend prudential target; finanancial stability; bank dividends